Analysis of Public Opinion on the Impact of the Implementation of Community Activity Restrictions (PPKM) During the Covid-19 Pandemic Using Long Short Term Memory and Latent Dirichlet Allocation - Gebyar Bintang Taufikurohman; Alamsyah Alamsyah (Universitas Negeri Semarang, 2023)
Technology social is the fastest and most up-to-date source of information. A model that can provide mapping will help in sorting out information more precisely and quickly. Public opinion in the mass media always develops quickly to talk about an issue in just a few days or even hours, so we do not know what the opinions of the people in the mass media are on the issue. In this study, the author applied topic modeling to the results of sentiment analysis on PPKM. The source of data in this study was obtained from twitter using SNScrape. The collected data was analyzed sentiment using the Long Short-term Memory (LSTM) method, so that public opinion was obtained with positive, negative, and neutral sentiments. The classification obtained from the results of the sentiment analysis process is continued with the topic modeling process using the Latent Dirichlet Allocation (LDA) method and visualized in the form of a wordcloud to find out the relationship between one topic and another. The sentiment analysis process produces a model with an accuracy rate of 90.8% and the topic modeling process successfully presents topics that are easy to interpret so that conclusions can be known about an issue.